Comorbidity and performance status as independent prognostic factors in patients with head and neck squamous cell carcinoma. Issue 5 (25th June 2015) - Wang, Jennifer R.; Habbous, Steven; Espin–Garcia, Osvaldo; Chen, Duoduo; Huang, Shao Hui; Simpson, Colleen; Xu, Wei; Liu, Fei‐Fei; Brown, Dale H.; Gilbert, Ralph W.; Gullane, Patrick J.; Irish, Jonathan C.; et al.
Abstract: Background: The purpose of this study was to evaluate the individual and combined relationship of comorbidity and performance status (PS) on head and neck squamous cell carcinoma (HNSCC) survival. Methods: Six hundred patients with HNSCC were prospectively recruited. Comorbidity and PS were measured using the Charlson Comorbidity Index (CCI) and the Eastern Cooperative Oncology Group (ECOG) Scale. Outcomes were overall survival (OS) and cancer‐specific survival (CSS). Results: A total of 48.3% of the patients had at least 1 comorbidity, and 42.3% had impaired PS at baseline. There was no correlation between CCI and ECOG (Spearman's ρ = 0.033; p = .42). In multivariate analysis, CCI score was significantly associated with OS ( p = .01). ECOG was not associated with OS, but seems to act as an effect modifier in the association between comorbidity and OS. CCI and ECOG were not associated with CSS. Conclusion: CCI and ECOG scores both provide prognostic information in predicting OS in HNSCC, but a significant association with CSS was not observed. © 2015 Wiley Periodicals, Inc. Head Neck 38: 736–742, 2016